Predation on microcrustaceans in evidence: the role of chaoborid larvae and fish in two shallow and small Neotropical reservoirs - Câmara,Carolina Figueira (2012)
This study was focused on the predation upon microcrustaceans by an invertebrate predator (chaoborid larvae), and vertebrate predators (fish), in two small reservoirs in southeastern Brazil, with and without macrophytes, in two climatic periods (dry and rainy seasons). Chaoborus larvae were sampled in the limnetic zone, as they are scarce in the littoral, and fish in both limnetic and littoral zones. Their diets were evaluated by the analysis of the crop (chaoborid) or stomach contents (fish). Chaoborid larvae consumed the dinoflagellate Peridinium sp. or other algae, rotifers, and planktonic microcrustaceans. The fish species that included microcrustaceans in their diets were juveniles caught in the littoral. Aquatic insects, plant fragments, and detritus were their major dietary items, microcrustaceans representing a minor item. Planktonic copepods contributed more to the diet of chaoborid larvae than planktonic cladocerans. Fish preyed on planktonic microcrustaceans, as well as on benthic and macrophyte-associated species. Microcrustaceans were not heavily preyed on by chaoborid larvae and fish in both reservoirs.